Peran Komunikasi Multimedia Dalam Industri Pariwisata Ekonomi Kreatif Pada Desa Wisata Puncak Aua Sarumpun - edlina, ria; Defhany; Fitri , Kintan Rahmi; Martin, Robi (CV. ITTC INDONESIA, 2023)
This research aims to determine the role of multimedia communication in the creative economy tourism industry in the Puncak Aua Sarumpun tourist village.